Fractional Order Image Processing of Medical Images - Bento, Tiago; Valério, Duarte; Teodoro, Pedro; Martins, Jorge (Journal of Applied Nonlinear Dynamics, 2026)
To perform a robot-assisted surgery of a prosthesis implantation on a patient’s femur, we may need to get the femoral head-neck orientation for the application. We can extract that information from Computed Tomography scans, using image processing. In image processing, edge detection often makes use of integer-order differentiation operators (e.g. Canny and LoG operators). This paper shows that introducing non-integer (fractional) differentiation to edge detectors (Fractional Canny, Fractional LoG, Fractional Derivative operators) can improve automatic edge detection results.